Pembuktian Penetapan Kualifikasi Penyalah Guna, Pecandu Dan Korban Penyalahgunaan Narkotika - Jetty Martje Patty; Veral Hendrisco Pattipeilohy (JURNAL BELO, 2019)
Proof plays a role in determining the qualification abusers, and victims of drug abuse. Proof is based on the book of the law of criminal procedure, with due regard to the evidence tool. Evidence set forth in the criminal procedure law is the testimony of witnesses,expert testimony, letters, instruction testimony of the defendant.